2003
DOI: 10.1021/jf0344486
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Antioxidant Properties ofLaurocerasus officinalisRoem. (Cherry Laurel) Fruit Grown in the Black Sea Region

Abstract: Laurocerasus officinalis Roem. is a summer fruit highly characteristic of the Black Sea region. The edible parts of the fruit were tested for chemical composition and antioxidant properties. Total moisture, ash, protein, sugar, pectin, ascorbic acid, phenolic, and mineral contents of the fruit were determined. The antioxidant activity of the fruit was investigated using TLC plate and ferric thiocyanate methods. Its antioxidative character was also tested utilizing hydroxyl, DPPH, and superoxide radical scaveng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
1
10

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 31 publications
(35 reference statements)
2
57
1
10
Order By: Relevance
“…Consequently, L. officinalis fruit extract provided protective effects against oxidative stress induced by dimethoate exposure. This may be reason that the antioxidant properties of L. officinalis fruit [15,19,20] and its hepatoprotective effect on rat liver toxicity induced by carbon tetrachloride [40] have been reported by the previous studies. In recent times, there is an attention for the significance of antioxidant compounds such as phenolic compounds present in the plants, which prevent toxic effects of free radicals because of their radical scavenger efficacy and have beneficial on human health [41] .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Consequently, L. officinalis fruit extract provided protective effects against oxidative stress induced by dimethoate exposure. This may be reason that the antioxidant properties of L. officinalis fruit [15,19,20] and its hepatoprotective effect on rat liver toxicity induced by carbon tetrachloride [40] have been reported by the previous studies. In recent times, there is an attention for the significance of antioxidant compounds such as phenolic compounds present in the plants, which prevent toxic effects of free radicals because of their radical scavenger efficacy and have beneficial on human health [41] .…”
Section: Discussionmentioning
confidence: 90%
“…(Cherry laurel) is grown as a native fruit in the coasts of the Black Sea region of Turkey and locally called "Taflan" or "Karayemiş" [13] . It was found that L. officinalis fruit is a rich source of antioxidant substances such as phenolics (chlorogenic acid, phenolic acids, anthocyanins, vanillic acid) and ascorbic acid [14][15][16][17][18][19][20] . Some studies indicated that L. officinalis fruit has radical scavenging action against superoxide and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals [15,19,21] .…”
Section: Introductionmentioning
confidence: 99%
“…Water distilled from the leaves is used as an almond flavoring and perfumery (Baytop, 1984, Ayaz et al, 1997Kolayli et al, 2003;Ercisli, 2004;Colak et al, 2005;Liyana-Pathirana et al, 2006;Celik et al, 2011;Beyhan, 2010;Islam et al, 2010;Anonymous, 2014). In Turkey, many researchers have done on cherry laurel on the content of chemicals, antioxidants, quality attributes, selection and long term pollen storage of non-sprayed genotypes (Kolayli et al, 2003;Beyhan, 2010;Islam et al, 2010;Sulusoglu, 2011, Celik et al, 2011Yıldız et al, 2014;Sulusoglu, 2014). Good yielded and palatable fruited trees of the cherry laurel grown around the Black Sea coastal, farmyard and forest area selected by inhabitants and propagated by longer cuttings over hundreds of years.…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds are ubiquitous in plants and are the largest secondary metabolite derivatives of the pentose phosphate, shikimate and phenylpropanoid pathways 2 . Composition and amount of phenolic substances depend on genetic and numerous environmental factors 3 . These play an important role in growth and reproduction, as well as providing protection against pathogens and predators, in addition to contributing towards the color and sensory characteristics of fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%